Pemerasan dalam Jabatan sebagai Bentuk Penyalahgunaan Wewenang : Perbandingan Hukum Kebijakan Kriminal di Indonesia dan Singapura - Cassis Merinthia Ariapramuda; Atik Winanti (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Abuse of position through extortion constitutes a form of power misuse that significantly undermines public integrity and trust in government. This study aims to analyze the regulation of extortion in office within the legal systems of Indonesia and Singapore, and to compare the criminal policies of both countries. The research employs a normative legal approach with doctrinal and comparative methods, examining legislation, jurisprudence, and relevant legal literature. The findings indicate that Indonesia emphasizes the elements of abuse of power and coercion as a formal offense under Article 12 letter e of the Corruption Eradication Law (UU Tipikor), whereas Singapore focuses on corrupt intent and the receipt of gratification under the Prevention of Corruption Act (PCA) 1960, without requiring coercion. In terms of criminal policy, Indonesia predominantly applies a repressive penal approach, while Singapore implements an integrated penal and non-penal strategy, emphasizing prevention, integrity development, and transparency in public administration. These findings highlight the necessity for legal and criminal policy reform in Indonesia through the strengthening of non-penal mechanisms, regulatory harmonization, and enhanced anti-corruption institutions, so that criminal law can function as ultimum remedium in safeguarding the integrity of public office